New methods for the arylation of trivalent phosphorus species and Studies towards the synthesis of sesqui-lignan natural products - Fearnley, Adam (2017)
Chapter one describes two efficient synthesis methods for the preparation of functionalised phosphonium salts. The first method utilises aryl radicals generated by a photo-induced decomposition of diaryliodonium salts, with the second method generating aryl radicals from arylboronic acids and manganese acetate. In both cases a broad substrate scope is demonstrated with respect to both the phosphorus and arylating species.